2017
DOI: 10.1038/s41598-017-12813-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic and genome-wide investigations of Vietnam ethnic groups reveal signatures of complex historical demographic movements

Abstract: The territory of present-day Vietnam was the cradle of one of the world’s earliest civilizations, and one of the first world regions to develop agriculture. We analyzed the mitochondrial DNA (mtDNA) complete control region of six ethnic groups and the mitogenomes from Vietnamese in The 1000 Genomes Project (1000G). Genome-wide data from 1000G (~55k SNPs) were also investigated to explore different demographic scenarios. All Vietnamese carry South East Asian (SEA) haplotypes, which show a moderate geographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…Kinh has been known to originate from northern Vietnam. Recent phylogenetic studies revealed that the majority of Kinh originated from South China and a minority from Thailand and Indonesia 27 . Therefore, the low prevalence of detectable GJB2 variants could be viewed as the genetic similarity between the Kinh people and the people from southern parts of China.…”
Section: Discussionmentioning
confidence: 99%
“…Kinh has been known to originate from northern Vietnam. Recent phylogenetic studies revealed that the majority of Kinh originated from South China and a minority from Thailand and Indonesia 27 . Therefore, the low prevalence of detectable GJB2 variants could be viewed as the genetic similarity between the Kinh people and the people from southern parts of China.…”
Section: Discussionmentioning
confidence: 99%
“…The linguistic and geographic diversity found in Vietnam might have influenced the genetic diversity in this area, such as the mitochondrial DNA (mtDNA) variation in Vietnamese populations. However, most previous studies of Vietnamese mtDNA variation have sequenced only the hypervariable segments of the control region, and there are only a few complete mtDNA sequences available from Vietnamese populations 5 8 . New advances in next-generation sequencing have made it feasible to sequence and analyze large numbers of complete mtDNA genomes 9 11 , and we have used these methods to obtain complete mitochondrial genomes from 609 unrelated Vietnamese subjects that encompass all five language families (Figure S1 , Online Resource 2).…”
Section: Introductionmentioning
confidence: 99%
“…On the maternal side, Li et al reported the Kinh Vietnamese have high frequencies of maternal mtDNA haplogroup B (B*, 4.2%; B4, 10.5%; B5, 6.3%), F (F*, 10.4%; F1a, 18.8%), M7b (M7b*, 8.3%; M7b1, 8.3%), and R (R*, 2.1%; R9b, 6.3%) (Li et al, ). Pischedda et al reported the typical Southeast Asian mtDNA lineages predominate in the Vietnamese, for example, haplogroup M7 comprises 20%, M(×D,C) comprises 29%, R9'F reaches 27%, and haplogroup B accounts for 25% (Pischedda et al, ). Pischedda et al also proposed the Vietnamese are an admixture of an East Asian component from south China and a southern Asian ancestral composite represented by the Malay 800 years ago using genomic data (Pischedda et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pischedda et al reported the typical Southeast Asian mtDNA lineages predominate in the Vietnamese, for example, haplogroup M7 comprises 20%, M(×D,C) comprises 29%, R9'F reaches 27%, and haplogroup B accounts for 25% (Pischedda et al, ). Pischedda et al also proposed the Vietnamese are an admixture of an East Asian component from south China and a southern Asian ancestral composite represented by the Malay 800 years ago using genomic data (Pischedda et al, ). Although a few genome‐wide studies of Vietnamese have been conducted so far, the genomic and mtDNA data for Jing people are never reported before.…”
Section: Introductionmentioning
confidence: 99%